The role of tourism, trade, renewable energy use and carbon dioxide emissions on economic growth:evidence of tourism-led growth hypothesis in EU-28 - Balsalobre-Lorente, Daniel (2020)
The article examines the effects of renewable energy, trade, carbon dioxide emissions and international tourism on economic growth in EU-28, considering panel data for the period 1995-2014. The investigation finds the new determinants of economic growth. The empirical results find support from the panel fully modified least squares (FMOLS), panel dynamic least squares (DOLS) and fixed effects (FE) as estimation techniques. The econometric results are consistent with the existing literature. The variables considered in this study are cointegrated in the first difference, as suggested by the panel unit root test. The present study seeks to advance the knowledge of the growth determinants, paying attention to the effect that both the tourism and energy sector exerts on economic growth for EU-28 countries. The empirical results demonstrate that trade openness, tourism arrivals and renewable energy encourage economic growth. Therefore, according to the econometric results, renewable energy allows improving environmental quality. However, CO2 emissions are positively correlated with economic growth, showing that growth is directly correlated by climate change and greenhouse gas. The results also confirm the tourism-led growth hypothesis (TLGH) for the panel. Finally, the empirical results confirm that trade openness, energy use and international tourism contribute to enhance economic growth. Based on these findings, further insights and policy prescription are offered in the concluding section.Graphical abstract.